ANALISIS GASTRODIPLOMASI MELALUI SAMYANG CHALLENGE TERHADAP DIPLOMASI KOREA SELATAN DI INDONESIA TAHUN 2015-2017 - Meganingratna, Andi; Anugrahningtyas, Wilda (Jurnal Ilmiah Hubungan Internasional Fajar, 2023)
The development of diplomatic relations between countries raises a new concept, namely gastrodiplomacy. This change was also adopted by the South Korean government, who used gastrodiplomation as one of the elements of Korean Wave through the Samyang Challenge trend. This study aims to see how the influence of the Samyang Challenge on the diplomacy process carried out by South Korea in Indonesia 2015 to 2017. Using the qualitative method and data reduction analysis, this study shows that this trend is sufficient to have a significant influence on South Korean diplomacy processes in Indonesia, although there are still further challenges, especially regarding product halal issues.